Molecular characterization of filamentous fungi associated with spoilage of sweet oranges sold in Choba Market, Port Harcourt, Nigeria (Asian Journal of Agriculture, 2023)
Abstract. Ikechi-Nwogu CG, Odogwu BA, Edumasam MA. 2023. Molecular characterization of filamentous fungi associated with spoilage of sweet oranges sold in Choba Market, Port Harcourt, Nigeria. Asian J Agric 7: 52-56. Post-harvest spoilage of sweet oranges is one of the major causes of post-harvest losses. This study was conducted to identify the fungi associated with post-harvest spoilage of sweet oranges using molecular techniques in Choba Markets, Rivers State, Nigeria. The DNA of the fungal isolate SO-1 and SO-2 were characterized using Internal Transcribed Spacer 4 and 5 molecular markers and aligned by the Basic Local Alignment Search Tool for Nucleotide (BLASTN) 2.8.0 of National Centre for Biotechnology Information (NCBI) database. Based on the sequence similarities, it was observed that isolate SO-1 was 98.96% identical to Neurospora crassa Shear & B.O.Dodge while SO-2 was 99.48% identical to Aspergillus flavus Link. These findings showed that N. crassa and A. flavus are some of the causal fungal pathogens of spoilt sweet oranges. It is anticipated that this result will provide information that will be helpful in the deployment of the appropriate post-harvest management of these fungi during post-harvest handling to minimize the spoilage of sweet oranges and thus reduce post-harvest losses.
Keywords: Aspergillus flavus, Choba Market, Neurospora crassa, RBCL marker, spoilage, sweet orange